Actual theoretical models of self-control: a narrative revision of Baumeister’s and Fujita’s models - Fiorentino, Federico Luis (2025)
Self-control is a relevant concept for understanding human behavior across different areas of life. It is associated with positive aspects in various domains and has a pragmatic value as a prerequisite for the successful achievement of long-term goals. In this regard, there are different theories and approaches to the study of self-control. Gaining a deeper understanding of the psychological mechanisms involved in this capacity could guide the design of more effective strategies to foster its development across different contexts. This narrative review article focuses on an updated overview of two of the main theoretical models of this construct, identifying potential similarities and differences. First, Roy F. Baumeister’s model proposes that self-control is a limited resource similar to a muscle. Self-control fatigue is known as “ego depletion”. Second, Kentaro Fujita’s model suggests that self-control is influenced by the way people mentally represent future events and decisions. The main findings of this review conclude that Baumeister’s and Fujita’s models offer distinct but complementary conceptualizations and perspectives on self-control. Each provides valuable insights into its functioning and potential for development. Furthermore, current research is moving toward an integrative model of effortful control and the study of meta-motivation, reflecting the evolution and enrichment of the understanding of this construct.